2015
DOI: 10.5585/conssaude.v13n4.4901
|View full text |Cite
|
Sign up to set email alerts
|

A órtese não influencia no desempenho de indivíduos com instabilidade do tornozelo

Abstract: Introdução: A instabilidade funcional do tornozelo (IFT) é uma das consequências das entorses de tornozelo, que podem gerar déficits de funcionalidade. Um dos métodos utilizados para avaliar esses déficits são testes funcionais (TF), além disso, pode-se prevenir a entorse usando órteses de tornozelo, no entanto, ambos os métodos ainda são controversos na literatura. Objetivo: Comparar o desempenho de indivíduo com e sem IFT em testes funcionais com e sem o uso da órtese de tornozelo. Método: Vinte e duas volun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Still, according to the research, 50% have no desire to have sexual intercourse, but even so, they claim to remain sexually active. Studies conducted by and Marques et al (2015) showed that, even after 60 years old, there is still a personal interest, that in this phase of life, unlike youth, sexual intercourse happens less frequently, valuing more the quality, the touch, affection, and complicity.…”
Section: Discussionmentioning
confidence: 99%
“…Still, according to the research, 50% have no desire to have sexual intercourse, but even so, they claim to remain sexually active. Studies conducted by and Marques et al (2015) showed that, even after 60 years old, there is still a personal interest, that in this phase of life, unlike youth, sexual intercourse happens less frequently, valuing more the quality, the touch, affection, and complicity.…”
Section: Discussionmentioning
confidence: 99%
“…Still, according to the research, 50% have no desire to have sexual intercourse, but even so, they claim to remain sexually active. Studies conducted by and Marques et al (2015) showed that, even after 60 years old, there is still a personal interest, that in this phase of life, unlike youth, sexual intercourse happens less frequently, valuing more the quality, the touch, affection, and complicity.…”
Section: Discussionmentioning
confidence: 99%
“…Still, according to the research, 50% have no desire to have sexual intercourse, but even so, they claim to remain sexually active. Studies conducted by and Marques et al (2015) showed that, even after 60 years old, there is still a personal interest, that in this phase of life, unlike youth, sexual intercourse happens less frequently, valuing more the quality, the touch, affection, and complicity.…”
Section: Discussionmentioning
confidence: 99%